Pengembangan Spot Wisata Bamboo-Construction di Rest Area Pagersari Kecamatan Ngantang Kabupaten Malang - Dian Ariestasi; M. Musthofa Al Ansyorie; Muhammad Aris Ichwanto; Dzul Fikri Muhammad; Alviando Galih Syahdandi; Mohammad Andyko (Jurnal Ekonomi, Bisnis dan Pendidikan (JEBP), 2023)
Abstract Pagersari Village is one of the villages in the administrative area of Ngantang Subdistrict, Malang Regency. Pagersari Village is located on the edge of Ngantang Subdistrict, more precisely on the Malang Regency and Blitar Regency border. Pagersari Village has potential derived from natural resources, most forests. Looking at the existing potential, the opportunity to make Pagersari Village a village not left behind can be wide open. Judging from the layout of Pagersari Village, which is located on the border of the regency and is heavily traversed by residents who want to go to Blitar Regency or vice versa, a rest area facility is needed. Judging from the conditions of the area above, it has the potential to fulfill the needs of the Rest Area. However, the development of rest areas in Pagersari village is still relatively lacking due to limited tourist spots. With the development of bamboo construction tourist spots, it is hoped that visitors to the rest area can increase to open opportunities to improve the surrounding community's economy. Abstrak Desa Pagersari merupakan salah satu desa yang berada dalam kawasan administratif Kecamatan ngantang Kabupaten Malang. Desa Pagersari adalah desa yang terletak di pinggir Kecamatan Ngantang lebih tepatnya terdapat di perbatasan Kabupaten Malang dengan Kabupaten Blitar. Desa Pagersari memiliki potensi yang berasal dari sumber daya alam yang sebagian besar wilayahnya berupa hutan. Dengan melihat potensi yang ada tersebut maka peluang untuk bisa menjadikan Desa Pagersari menjadi desa yang tidak tertinggal dapat terbuka lebar. Dilihat dari tata letak Desa Pagersari yang terdapat pada perbatasan kabupaten dan banyak dilalui oleh warga yang ingin menuju Kabupaten Blitar ataupun sebaliknya maka diperlukan adanya fasilitas berupa rest area. Dilihat dari kondisi daerah di atas, maka sangat berpotensi untuk pemenuhan kebutuhan Rest Area. Namun, saat ini pengembangan rest area pada desa pagersari masih tergolong kurang karna terbatasnya spot untuk wisata. Dengan adanya pengembangan spot wisata bamboo construction diharapkan pengunjung rest area dapat bertambah banyak sehingga dapat membuka peluang peningkatan ekonomi masyarakat sekitar.